2019
DOI: 10.21203/rs.2.10815/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accessibility of basic paediatric emergency care in Malawi: analysis of a national facility census

Abstract: Background Emergency care is among the weakest parts of health systems in low-income countries with both quality and accessibility constraints. Previous studies estimated accessibility to surgical or emergency care based on population travel times to nearest hospital with no assessment of hospital readiness to provide such care. We analysed a Malawi national facility census with comprehensive inventory audits and geocoded facility locations to identify hospitals equipped to provide basic paediatric emergency c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…41 Availability of injectable adrenaline ranged between 6•1% across Africa to 62•1% in Malawi. 23,32 Adrenaline was affordable in the one study from Nigeria that reported it with 0•3 days' wages required. 41 Most studies were cross-sectional observational studies that used various recommended WHO methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…41 Availability of injectable adrenaline ranged between 6•1% across Africa to 62•1% in Malawi. 23,32 Adrenaline was affordable in the one study from Nigeria that reported it with 0•3 days' wages required. 41 Most studies were cross-sectional observational studies that used various recommended WHO methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…The guidelines follow the ABCD concept (Airways-Breathing-Circulation, Coma, Convulsion-Dehydration) and priority signs as shown in Fig 1. These are an integral part of the IMCI system to reduce childhood illness [24]. Following the success of integrating ETAT into health programmes to improve paediatric triage training in 8 tertiary and secondary level hospitals [23], ETAT has since been introduced to more than 54 hospitals in Malawi, including QECH, resulting in a process of rapid triage for all children to determine whether any emergency or priority signs are present, followed by prompt emergency treatment [25,26].…”
mentioning
confidence: 99%